¿Influyen los valores hacia la pareja sobre la violencia sufrida en el noviazgo adolescente? (2021)
Introduction. Research on adolescent intimate partner violence has been increasing in recent years. However, there are few studies that delve into the role of cultural values and preferences associated with the partner in the possibility of suffering violence. This research aims to analyze the different value profiles towards the adolescent partner and subsequently to analyze the influence of these on violence victimization. Method. A questionnaire on adolescent intimate partner violence and associated cultural aspects was applied to 417 Spanish adolescents (15-21 years old) who had been in an active relationship for the last 3 months. Results. Jealousy and control appear as the most widespread forms of violence and sexual violence is the only form of violence with differencesattributable to gender. The analysis of the values associated with the couple shows that women value more communicative aspects in the couple and men value appearance. Women prefer, to a greater extent than men, to have fun, to be free and to feel desired. The valuational differences were grouped into three relational profiles or clusters: the traditional-communicative, the hedonistic-detached and the protectivedependent. Finally, contrast tests denied a direct influence of partnerassociated values on intimate partner violence victimization.Conclusions. The analysis of the values associated with the coupleprovides rich information on the transformations that are taking place inadolescent relationships, but does not maintain a direct relationship withthe violence suffered.